2014
DOI: 10.1016/j.annemergmed.2013.12.019
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Electronic Health Record Implementation on Community Emergency Department Operational Measures of Performance

Abstract: Objective To study the effect of electronic health record (EHR) implementation on the operational metrics of a diverse group of community emergency departments (ED). Methods We performed a retrospective before/after analysis of 23 EDs from a single management group that experienced EHR implementation, defined as the date of implementation of electronic clinical documentation in the ED. We obtained electronic data for 4 length-of-stay (LOS) measures (arrival-to-provider, admitted, discharged and overall LOS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…However, laboratory testing, medication administration and radiologic imaging all showed sustained increase-post-implementation 82. In a further study, no difference was found in measures of operational performance,83 and others also report no effect on outpatient volumes84 or readmission rates 85. The most recent emergency department study reported no differences in volume, admissions, or transfers but increased length of stay until 1 year later 86…”
Section: Resultsmentioning
confidence: 92%
“…However, laboratory testing, medication administration and radiologic imaging all showed sustained increase-post-implementation 82. In a further study, no difference was found in measures of operational performance,83 and others also report no effect on outpatient volumes84 or readmission rates 85. The most recent emergency department study reported no differences in volume, admissions, or transfers but increased length of stay until 1 year later 86…”
Section: Resultsmentioning
confidence: 92%
“…29,30 Frequently, the timeliness of care is transiently increased before returning to preimplementation levels. 31 In this study, we found an independent association of post-EMR implementation with decreased total ED length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…56 Early work has not demonstrated an operations benefit for community EDs that have invested in electronic medical records. 57 Better information technology infrastructure, using tools from predictive analytics, may be necessary to realize gains from that investment. Overall, many aspects of emergency care might benefit from new-wave predictive analytics.…”
Section: Opportunities In Emergency Carementioning
confidence: 99%
“…Use of clinical decision tools has historically been low, 78,79 whereas early evidence has failed to demonstrate the value of electronic medical record data in ED operations. 57 Clinicians have cited performance reproducibility, cumbersome implementation, and exclusion of and inferiority to clinician gestalt as reasons for this. [80][81][82] Some barriers may be more easily addressed with new-wave predictive tools.…”
Section: Clinical Uptakementioning
confidence: 99%